Performance evaluation of LoRa and ZigBee technologies applied to FANETs - Ferreira, Leonardo Costa; Silva, Luis Claudio Batista Da; Rosa, Paulo Fernando Ferreira (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2021)
Wireless communication technologies are applied in different activities and performance evaluations are important issues. This paper presents a comparison of transmission rate and packets delivery rates between LoRa and ZigBee technologies, whose main interest is to investigate the performance in ad hoc networks, especially in flying ad hoc networks (FANET). Hardware-in-the-loop bench scale and human-in-the-loop ground scale experiments were performed for the LoRa RD42C and XBee-PRO S3B radios, regarding their transmission rate and packets delivery rates on the bench and at distances ranging from 100 to 500m, using different transmission rates, powers and scattering factors. The results indicate that the XBee radio outperformed the LoRa radio on the bench in terms of transmission transfer rate and delivery at the analyzed potencies. In ground experiments, XBee was more efficient than LoRa overall, but only up to 300m at 21dBm.